2006
DOI: 10.1007/s00199-004-0551-z
|View full text |Cite
|
Sign up to set email alerts
|

Interest rate rules, inflation and the Taylor principle: an analytical exploration

Abstract: The purpose of this article is to characterize optimal interest rate rules in the framework of a dynamic stochastic general equilibrium model, and notably to scrutinize the “Taylor principle”, according to which the nominal interest rate should respond more than one for one to inflation. This model yields explicit solutions for the optimal rule. We find that the elasticity of response depends on numerous factors, such as the degree of price rigidity, the autocorrelation of the underlying shocks, or which measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus 'market' prices are never supporting Walrasian equilibria in the traditional meaning. Individual markets can balance excess demand and excess supply (for a macro-economic perspective, see Bénassy 2006). 4 Electricity provision is an example of the 'no exit constraint'.…”
Section: The Drèze-stern Social Cost-benefit Settingmentioning
confidence: 99%
“…Thus 'market' prices are never supporting Walrasian equilibria in the traditional meaning. Individual markets can balance excess demand and excess supply (for a macro-economic perspective, see Bénassy 2006). 4 Electricity provision is an example of the 'no exit constraint'.…”
Section: The Drèze-stern Social Cost-benefit Settingmentioning
confidence: 99%
“…Generally speaking, to the extent that lower real interest rates stimulate economic activity and inflation, if 1 β > , interest rate rules will tend to be stable, while if 1 β < , interest rate rules are expected to be unstable. Benassy (2006) constructed a dynamic stochastic general equilibrium model to get an optimal interest rule, and found that elasticity of response depends on several factors, such as the degree of price rigidity, the autocorrelation of the underlying shocks, or which measure of inflation is used. In general, the optimal elasticity of the interest rate with respect to inflation needs not to be greater than 1, that is 1…”
mentioning
confidence: 99%
“…China Inter-bank Offered Rate: 1994-2006 measure of historical analysis. In the historical analysis, we choose the data of CPI from 1994 to 2006 to calculate the inflation rate, the mean of which is 4.5%, and the median is 1.4%.…”
mentioning
confidence: 99%